STATE YOUTH POLICY AS THE BASIS OF SOCIO-ECONOMIC DEVELOPMENT - N. Eshmurodov; A. Khujamkulov (American Journals Publishing, 2023)
In this article, the author approached the topic of youth as a priority direction of state social policy, and the problem of youth is one of the most pressing today. The article analytically highlights that this socio-demographic layer of the population is the main criterion for the implementation of state policy.
Keywords: Youth, youth policy, Youth Affairs Agency, youth rights, youth balance, youth issue.